STRUCTURAL SYNTHESIS OF A SIX-LINK PERCUSSION MECHANISM WITH THE LARGEST ROCKER ARM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this paper, we consider the synthesis of a six-link impact mechanism with the largest rocker arm with improved kinematic and dynamic parameters based on a crank-rocker and two-crank hinged-four-bar mechanisms with special positions of the links.
Keywords: Special position, link, connecting rod, mechanism, synthesis